2018
DOI: 10.1021/acs.chemmater.8b02222
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Core Size on Performance of Fused-Ring Electron Acceptors

Abstract: We report 4 fused-ring electron acceptors (FREAs) with the same end-groups and side-chains but different cores, whose sizes range from 5 to 11 fused rings. The core size has considerable effects on the electronic, optical, charge transport, morphological, and photovoltaic properties of the FREAs. Extending the core size leads to red-shift of absorption spectra, upshift of the energy levels, and enhancement of molecular packing and electron mobility. From 5 to 9 fused rings, the core size extension can simultan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
88
0
1

Year Published

2019
2019
2021
2021

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 107 publications
(90 citation statements)
references
References 49 publications
1
88
0
1
Order By: Relevance
“…The ternary approach, by introducing a smaller bandgap nonfullerene acceptor as a near infrared (NIR) absorber to increase the device J sc of fullerene‐free binary blended material systems, hereafter named as the “current‐increased” strategy, has received an increasing interest recently . First, homogeneous acceptor phases can be facilely formed due to their structural similarity between the selected two nonfullerene acceptors .…”
Section: Introductionmentioning
confidence: 99%
“…The ternary approach, by introducing a smaller bandgap nonfullerene acceptor as a near infrared (NIR) absorber to increase the device J sc of fullerene‐free binary blended material systems, hereafter named as the “current‐increased” strategy, has received an increasing interest recently . First, homogeneous acceptor phases can be facilely formed due to their structural similarity between the selected two nonfullerene acceptors .…”
Section: Introductionmentioning
confidence: 99%
“…Nevertheless, two recent reports suggested that an increasing number of heterocyclic rings beyond 8–9 rings does not further extend the absorption . Besides, FREAs with larger core have similar electrochemical properties suggesting that further increase in the number of rings does not translate into improved efficiency yet adding synthetic complexity.…”
Section: Nfas and Various Aspects Of Freasmentioning
confidence: 96%
“…The nanoscale morphology of the ternary blend found to be like the binary devices with both the FREAs showed excellent compatibility. Zhan and co‐workers also recently utilized a similar strategy to boost the V OC with an addition of the third component with higher LUMO level . A PCE of 12.6% was achieved using a blend of FTAZ: F9IC : F11IC due to efficient charge dissociation and collection enhancing both FF and J SC .…”
Section: Other Aspects Of Frea Oscsmentioning
confidence: 99%
“…Meanwhile, the D core also plays a key role in adjusting the Enormalgopts and energy levels of NFAs. For example, using a strong electron‐donating capacity D core can amplify the intramolecular charge transfer (ICT) effect for a narrow Enormalgopt . However, such a D core also leads to a high HOMO level, which not only astrict the option of donor material but also limit the increase in V oc .…”
Section: Introductionmentioning
confidence: 99%